2016
DOI: 10.1002/ajmg.a.37784
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sleep disturbances in Rett syndrome: Novel findings in relation to genotype

Abstract: Rett syndrome is a rare but severe neurological disorder associated with a mutation in the methyl CpG binding protein 2 (MECP2) gene. Sleep problems and epilepsy are two of many comorbidities associated with this disorder. This study investigated the prevalence and determinants of sleep problems in Rett syndrome using an international sample. Families with a child with a confirmed Rett syndrome diagnosis and a MECP2 mutation registered in the International Rett Syndrome Phenotype Database (InterRett) were invi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 47 publications
8
50
0
Order By: Relevance
“…2 & 3F). 169 Those with epilepsy and those not mobile were more likely to have excessive somnolence also consistent with earlier findings. 166 In one small clinical trial (n=9) melatonin appeared to improve total sleep time and efficiency in those worse at baseline without any adverse side effects.…”
Section: Sleep Disturbancessupporting
confidence: 87%
See 1 more Smart Citation
“…2 & 3F). 169 Those with epilepsy and those not mobile were more likely to have excessive somnolence also consistent with earlier findings. 166 In one small clinical trial (n=9) melatonin appeared to improve total sleep time and efficiency in those worse at baseline without any adverse side effects.…”
Section: Sleep Disturbancessupporting
confidence: 87%
“…167,168 A recent study, using InterRett for ascertainment, surveyed parents/carers of 364 genetically confirmed cases aged 2-57 years. 169 Night waking was frequent, and, consistent with previous research, those with the p.Arg294*were most likely to have problems initiating and maintaining sleep (see Figs. 2 & 3F).…”
Section: Sleep Disturbancessupporting
confidence: 81%
“…12 found in more than 80% of cases, may contribute to sleep disruption by dysregulation of neurological sleep networks. A similar frequency of sleep disturbance was observed in Rett syndrome, 15 although children with other developmental and epileptic encephalopathies need to be studied. Mouse models of SCN1A mutations have shown that the Na v 1.1 channel encoded by SCN1A is expressed in cells important for sleep regulation, including the GABAergic neurons in the hypothalamus, thalamic reticular nucleus, and cortex.…”
Section: Discussionmentioning
confidence: 60%
“…The high frequency of sleep disturbance may also be attributed to or compounded by refractory nocturnal seizures, and polypharmacy in children with Dravet syndrome. A similar frequency of sleep disturbance was observed in Rett syndrome, 15 although children with other developmental and epileptic encephalopathies need to be studied. Comorbidities, such as autistic features and developmental delay, frequently seen in children with Dravet syndrome, may also contribute to reports of high sleep disturbance in this population.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation